Implications of Using Different Definitions on Outcomes in Worsening Heart Failure. (August 2016) - Kelly, Jacob P.; Cooper, Lauren B.; Gallup, Dianne; Anstrom, Kevin J.; Chen, Horng H.; Redfield, Margaret M.; O'Connor, Christopher M.; Mentz, Robert J.; Hernanadez, Adrian F.; Felker, G. Michael
Abstract : Background—: In-hospital worsening heart failure (WHF) is an important event that has inconsistent definitions used across trials. We used data from 2 acute heart failure (HF) trials from the National Institutes of Health HF Network, DOSE (Diuretic Optimization Strategies Evaluation) and ROSE (Renal Optimization Strategies), to understand event rates associated with different WHF definitions. Methods and Results—: We pooled data from 668 patients in DOSE and ROSE and assessed the relationship between WHF and the composite end point of rehospitalization, emergency room visits for HF, and mortality through 60 days. We also assessed for a differential relationship between the timing of WHF development and outcomes. The overall incidence of WHF was 14.6% (24.1% in DOSE, 6.3% in ROSE, and 5.0% in DOSE using the ROSE definition). WHF was associated with an increase in the composite end point (hazard ratio [HR], 1.64; 95% confidence interval [CI], 1.11–2.42; P =0.01). However, the association between WHF and outcomes was significantly stronger in ROSE than in DOSE (HR, 2.67; 95% CI, 1.45–4.91; P <0.01 and HR, 1.28; 95% CI, 0.79–2.08; P =0.31, respectively). Development of WHF between baseline to 24 hours compared with 24 to 48 hours or 48 to 72 hours demonstrated a trend toward improved outcomes (HR, 0.49; 95% CI, 0.21–1.17; P =0.11 and HR, 0.45; 95% CI, 0.20–1.04; P =0.06, respectively). Conclusions—: A WHF definition that excluded the intensification of diuretics resulted in a lower event rate but a stronger association with outcomes. These data support the need for continued efforts to standardize WHF definitions in clinical trials. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT00577135 (DOSE) and NCT01132846 (ROSE).